Case Report of Ectopic Ovarian Pregnancy following Fresh Embryo Transfer - Nivin Samara; Yaakov Bentov (SAGE Publishing, 2016)
Background Ovarian pregnancy is a rare and challenging clinical phenomenon. Recent studies have identified assisted reproductive treatments and infertility as risk factors. However, neither a definite mechanism nor clear risk factors were identified and therefore prevention strategies are yet unavailable. Clinical Case In this article, we present a case of ovarian pregnancy occurring following in vitro fertilization treatment and a fresh embryo transfer. The couple was diagnosed with unexplained infertility and no identifiable risk factors for extrauterine pregnancy. The diagnosis of ovarian pregnancy was made during explorative laparoscopy performed due to suspected extrauterine pregnancy. The patient had normal intra- and postoperative course. Conclusion Ovarian pregnancy is an infrequent and a challenging diagnosis. Yet, late diagnosis and lack of appropriate intervention may have long-term implications. Several mechanisms and risk factors are proposed, and their acknowledgment may improve early diagnosis and prevention of complications.